Fast rigorous impedance matrix calculations in SDM for analysis of open planar structures - Balik, Hasan H.; Railton, C.J. (My University, 2002)
Spectral Domain Method (SDM) has been chosen to develop a technique which is accurate, yet retains the interactive design tool capabilities of a simpler method. In this paper several enhancements will be presented to speed up impedance matrix calculation which must be repeated at each spot frequency in SDM. In addition, an adaptive truncation which limits the numerical integration over an infinite surface to the finite computer resources will be introduced. The location vector calculation will also be presented in this contribution to reduce the number of impedance matrix elements to be calculated. Moreover a technique which cannot completely be classified one way or other will be introduced. This enhancement reduces the number of impedance matrix elements in one dimension and hence speeds up overall numerical integration.
Brzi strogi prora?un matrice impendancije kod metode spektralne domene u analizi otvorenih ravninskih struktura
Keywords: Impedance matrix calculation; Planar circuits; Spectral domain method (SDM)